Isoflavone Attenuates the Caspase-1 and Caspase-3 Level in Cell Model of Parkinsonism - Jian-xin Xu; Hai-ping Song; Qing-Xia Bu; De-Peng Feng; Xiao-Fan Xu; Qian-Ru Sun; Xue-Li Li (Behavioural Neurology)
The study has investigated the effect of isoflavone attenuates the caspase-1 and caspase-3 level in cell model of Parkinsonism. The subjects were PC12 cells. They were randomly divided into six groups: control, MPP+ (250 μmol/L), isoflavone (10 μM), isoflavone (10 μM) + MPP+ (250 μmol/L), Z-YVAD-CHO (10 nM) + MPP+ group, and Z-DEVD-CHO (10 nM) + MPP+ group. Cell viability was measured by MTT methods; the content of tyrosine hydroxylase was measured by immunocytochemistry method of avidinbiotin peroxidase complex; apoptosis ratio was measured by flow cytometry. The results showed that cell viability in the MPP+ group was lower than in all other five groups. There was no difference in cell viability between isoflavone + MPP+ and control group. Optical density of TH positive cells in isoflavone group was higher than in control, isoflavone + MPP+, and MPP+ only groups. The apoptosis ratio in the isoflavone + MPP+ group and control group and the Z-YVAD-CHO + MPP+ and Z-DEVD-CHO + MPP+ group was similar, which was lower than in the MPP+ group. The lowest apoptosis ratio was found in the isoflavone only group.